Ultraviolet B (UVB) Radiation Induces Skin Alterations, Emperipolesis and Decreases the Erythroid-to-myeloid Ratio in Rats - Farida, Verda; Dewananda, Dion Adiriesta; Sahid, Muhammad Novrizal Abdi; Salasia, Siti Isrina Oktavia (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Ultraviolet B (UVB) radiation is commonly known to be related to skin inflammation. The inflammation process is orchestrated by many cell types, including immune cells. Changes in bone marrow cellularity can also be an indicator of inflammation. Megakaryocytes, myeloid immune cells progenitor and erythroid progenitor cells, are at high risk of changes upon UVB irradiation. However, there are still limited study observing the change of bone marrow cell population after UVB irradiation. Therefore, this study was conducted to investigate the alteration of the skins, emperipolesis, and the change in erythroid and myeloid cell population in bone marrow after UVB irradiation.METHODS: Ten Wistar rats were divided equally into control and UVB-irradiated group. The skin superficial condition before and after UVB irradiation was observed with a skin analyzer camera. On the 9th day, skin tissues were processed for the observation of general skin structure with hematoxylin-eosin (HE) staining, mast cells infiltration with toluidine blue staining, and collagen fibers with Mallory staining. Bone marrow and peripheral blood samples were collected and proceeded for Giemsa-staining to observe the cell population.RESULTS: Erythema appeared on the skin as marked by orange-red spots. There were hyperkeratosis and pigment accumulations in the skin of UVB-irradiated group. The depletion of collagen-density and hemorrhage were clearly observed in the skin of UVB-irradiated group. There were higher mast cell numbers in the UVB-irradiated skin compared to non-treated skin. The erythroid-to-myeloid ratio in the bone marrow was decreased to around 1.6:11.2 from the normal ratio of 1:4. In addition, emperipolesis was observed in the bone marrow induces by UVB-irradiation.CONCLUSION: These results indicate that UVB-irradiation alters the skin structure, erythroid-to-myeloid ratio, and induced emperipolesis.KEYWORDS: emperipolesis, erythroid, myeloid, skin, UVB radiation